Facial Baroparesis Caused by Scuba Diving - Daisuke Kamide; Takeshi Matsunobu; Akihiro Shiotani (Case Reports in Otolaryngology)
Middle ear barotrauma is one of the common complications of SCUBA diving representing acute otalgia, hearing loss, and bleeding. But occurrence of facial palsy is rare. Here we report a case of a 30-year-old navy diver suffered middle ear barotrauma with transient facial palsy after SCUBA diving. He felt difficulty in equalizing the pressure in middle ear with Valsalva maneuver during diving, and suffered right facial palsy and aural fullness after diving. Clinical examination showed remarkable bulging of the right tympanic membrane and right facial palsy without other neurological findings. But facial palsy was disappeared immediately after myringotomy. We considered that the etiology of this case was neuropraxia of facial nerve in middle ear caused by over pressure of middle ear.